Distribution and Health Risk Assessment on Dietary Exposure of Polycyclic Aromatic Hydrocarbons in Vegetables in Nanjing, China. (29th August 2016) - Wu, Minmin; Xia, Zhonghuan; Zhang, Qianqian; Yin, Jing; Zhou, Yanchi; Yang, Hao
Abstract : In a market basket study made in Nanjing, China, in which the most common consumed nine kinds of vegetables foodstuffs were sampled, the contents of 16 polycyclic aromatic hydrocarbons (PAHs) were analyzed using gas chromatography with mass spectrometer detector (GC-MS). The results showed that the total amount of 16 PAHs was within the range of 60.5 312 ng g −1 (wet weight). The ranking of total concentrations for different types of vegetables in decreasing order was leafy vegetable, fruit vegetable, and rhizome vegetable. Source analysis suggested that coal, oil, or other incomplete combustion of biomass mainly contributed to the concentration of PAHs. The margin of exposure (MOE) approach with age/gender group-specific daily dietary exposure level was used to estimate the carcinogenic risk. The calculated total mean MOE in the case of BaP and PAH4 (sum of BaA, CHR, BbF, and BaP) was 14960 and 7723, respectively, for local residents. In addition, the MOEs in PAH4 for some groups of both male and female were below the critical limit of 10 000 proposed by EFSA. Therefore, health effect owing to the consumption of vegetables on local residents needs high concern.